Musical Skill Enhancement of Sunday School Kids through Pianika Ensemble Based on Bloom's Taxonomy Theory at GKE Hanggulan Sinta - Sihombing, Octa Maria; Simanjuntak, Nova Lady; Zebua, Vernike Niatda; Fransiska, Fransiska (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Music ensemble in Sunday School is the activity performed by Sunday School children. Playing music ensembles with spiritual songs adds insight, knowledge, develops creativity, learns to accept and respond to God's love and creation, trains psychomotor skills, builds good cooperation, and appreciates the differences that exist around children. This study aims to train and develop the ability of Sunday School children to play pianika music ensemble in the cognitive, affective and psychomotor domains. The method used was qualitative descriptive, the research was conducted at the Kalimantan Evangelical Church (GKE) Hanggulan Sinta. The results revealed an ensemble playing pianika music could foster togetherness, develop creativity, dare to express themselves, foster a sense of empathy within themselves, be disciplined and responsible for the tasks assigned. This study concludes on the development of Sunday School children's pianika music playing skills based on Bloom's taxonomy at GKE Hanggulan Sinta using the direct learning model can develop well, as seen in several phases in the direct learning model during the learning process. Furthermore, the results of coaching and learning pianika music ensembles are applied and displayed at major church activities, namely the commemoration of GKE Children's Day, general worship and categorical worship.